2019
DOI: 10.1186/s40001-019-0392-7
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison of bi- and tricortical k-wire fixation in tension band wiring osteosynthesis

Abstract: Background Patients with a simple transversal fracture of the olecranon are often treated with a tension band wiring (TBW), because it is known as a biomechanically appropriate and cost-effective procedure. Nevertheless, the technique is in detail more challenging than thought, resulting in a considerable high rate of implant-related complications like k-wire loosening and soft tissue irritation. In the literature, a distinction is generally only made between transcortical (bi-) and intramedull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Tension band fixation used for fracture compression in orthopedic trauma surgery was preferred to provide epiphysiodesis in the present study. [15,16] We found that the tension band technique performed with K wire and cerclage could control the growth in the epiphysis by the aid of the compression created in the physeal growth plate of the subjects and was as effective as 8-plate. One of the hypotheses of the present study was to reduce the cost of the implants used in surgical procedures.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Tension band fixation used for fracture compression in orthopedic trauma surgery was preferred to provide epiphysiodesis in the present study. [15,16] We found that the tension band technique performed with K wire and cerclage could control the growth in the epiphysis by the aid of the compression created in the physeal growth plate of the subjects and was as effective as 8-plate. One of the hypotheses of the present study was to reduce the cost of the implants used in surgical procedures.…”
Section: Discussionmentioning
confidence: 97%
“…The tension band fixation provides an advantage for fracture union by converting tensile forces into compressive forces. [15,16] In the present experimental animal study, we hypothesized that the surface where the tension band application with the K-wire creates pressure on the perichondrial ring would be lower than the 8-plate and K-wire would cause less damage to the perichondrial ring. We, therefore, aimed to develop a lower-cost technique that prevents angular deformities, does not cause permanent problems, and minimizes damage by reducing the pressure in the perichondrial ring, by using the tension band technique with a K-wire and cerclage, which are commonly used by orthopedic surgeons in clinical practice.…”
mentioning
confidence: 96%
“…This procedure ensures that the bone pieces are compressed dynamically and heal quickly. 5 Complications might arise, the most prevalent of which include hardware prominence that needs to be removed, mobility loss and fixation loss.…”
Section: Introductionmentioning
confidence: 99%
“…A similar technique of utilizing tricortical wire fixation for olecranon fractures has shown biomechanical superiority to bicortical wire fixation. 13 The purpose of this study was to biomechanically compare the fixation of a distal chevron osteotomy using tricortical K-wire fixation with traditional unicortical K-wire fixation and singlescrew fixation. We hypothesized that tricortical K-wire fixation is biomechanically superior to traditional unicortical K-wire fixation and equivalent to screw fixation in a cadaveric model.…”
mentioning
confidence: 99%
“…A similar technique of utilizing tricortical wire fixation for olecranon fractures has shown biomechanical superiority to bicortical wire fixation. 13…”
mentioning
confidence: 99%